The Association Between Cigarette Smoking and Carotid Intima–Media Thickness Is Influenced by the −930A/G CYBA Gene Polymorphism: The Cardiovascular Risk in Young Finns Study - Fan, M.; Raitakari, O.T.; Kähönen, M.; Juonala, M.; Hutri-Kähönen, N.; Pörsti, I.; Viikari, J.; Lehtimäki, T. (American journal of hypertension, 2009)
Background Smoking-induced damage to the cardiovascular system has been shown in many studies; however, the degree of damage varies from individual to individual. We hypothesized that the −930A/G CYBA gene polymorphism in the NADPH oxidase influences the association between cigarette smoking and carotid intima–media thickness (IMT) in young healthy adults. Methods Cross-sectional data obtained in 2001 for the Cardiovascular Risk in Young Finns Study were used. IMT was measured with ultrasound. The genotyping was performed using a 5′-nuclease assay. A linear regression model was used to test whether the interaction between smoking and the genotypes was associated with IMT. The magnitude of the interaction effect was further examined by performing a stratified analysis according to smoking habits. Results In the entire population, the mean and maxima IMT were higher in smokers than nonsmokers (P = 0.005 and 0.008, respectively). The differences were most significant in subjects with the GG genotype, borderline significant for the GA genotype, and nonsignificant for the AA genotype. The interaction of genotypes with smoking was associated with mean and maximal IMT (P = 0.042 and 0.022). Among smokers, subjects with the GG genotype had a higher mean and maximal IMT compared with carriers of the A allele (P = 0.021 and 0.012). In contrast, the mean and maximal IMT were lower for G allele carriers than subjects with the AA genotype among nonsmokers (P = 0.022 and 0.026). All results had been adjusted for potential risk factors related to IMT. Conclusion The −930A/G polymorphism modifies the association between cigarette smoking and IMT in young healthy adults. American Journal of Hypertension 2009; doi:10.1038/ajh.2008.349